Matematyka
karolina12041
2017-06-25 05:14:07
Bardzo krótkie zadanie z matematyki.
Odpowiedź
karo16161
2017-06-25 07:08:24

[latex]a) \ \ a=-2 \ b=3 \ c=-5 \ \ frac{a+b+c}{a-b+c}= frac{-2+3-5}{-2-3-5}= frac{1-5}{-5-5}= frac{-4}{-10}= frac{4}{10}= frac{2}{5} \ \ frac{a-b-c}{a-c}= frac{-2-3-(-5)}{-2-(-5)}= frac{-2-3+5}{-2+5}= frac{-5+5}{3}= frac{0}{3}=0 \ \ frac{b-c-a}{b+c}= frac{3-(-5)-(-2)}{3-5}= frac{3+5+2}{3-5}= frac{8+2}{-2}= frac{10}{-2}=-5 [/latex] [latex]b) \ \ x=-1frac{1}{2} \ y=- frac{1}{4} \ z=- frac{3}{4} \ \ frac{x-y+z}{x+y+z}= frac{-1 frac{1}{2}-(- frac{1}{4})- frac{3}{4} }{-1 frac{1}{2}- frac{1}{4}- frac{3}{4} } = frac{-1 frac{1}{2}+ frac{1}{4}- frac{3}{4} }{-1 frac{1}{2}-1 } = frac{-1 frac{1}{2}- frac{2}{4} }{-2 frac{1}{2} }= frac{-1 frac{1}{2}- frac{1}{2} }{-2 frac{1}{2} }= \ = frac{-2}{-2 frac{1}{2} }= frac{-2}{- frac{5}{2} } =-2*- frac{2}{5}=frac{4}{5} [/latex] [latex] frac{x-y}{y-z}= frac{-1 frac{1}{2}-(- frac{1}{4} ) }{- frac{1}{4}-(- frac{3}{4}) }= frac{-1 frac{1}{2} + frac{1}{4} }{- frac{1}{4}+ frac{3}{4} }=frac{-1 frac{2}{4}+ frac{1}{4} }{ frac{2}{4} }= frac{-1 frac{1}{4} }{ frac{2}{4} }=frac{- frac{5}{4} }{ frac{2}{4} }=\=- frac{5}{4}* frac{4}{2}=- frac{5}{2}= -2 frac{1}{2} [/latex] [latex] frac{x+y-z}{y+z}= frac{-1 frac{1}{2}- frac{1}{4}-(- frac{3}{4}) }{- frac{1}{4}- frac{3}{4} }= frac{-1 frac{1}{2}- frac{1}{4}+ frac{3}{4} }{-1}= frac{-1 frac{1}{2}+ frac{2}{4} }{-1}= frac{-1 frac{1}{2} + frac{1}{2} }{-1}=\= frac{-1}{-1}=1 [/latex]

Dodaj swoją odpowiedź